Cell shape-dependent shear stress on adherent cells in a micro-physiologic system as revealed by FEM. (9th April 2015) - Pfister, C; Bozsak, C; Wolf, P; Demmel, F; Brischwein, M
Abstract: Flow-induced shear stress on adherent cells leads to biochemical signaling and mechanical responses of the cells. To determine the flow-induced shear stress on adherent cells cultured in a micro-scaled reaction chamber, we developed a suitable finite element method model. The influence of the most important parameters—cell shape, cell density, shear modulus and fluid velocity—was investigated. Notably, the cell shape strongly influences the resulting shear stress. Long and smooth cells undergo lower shear stress than more rounded cells. Changes in the curvature of the cells lead to stress peaks and single cells experience higher shear stress values than cells of a confluent monolayer. The computational results of the fluid flow simulation were validated experimentally. We also analyzed the influence of flow-induced shear stress on the metabolic activity and shape of L929, a mouse fibroblast cell line, experimentally. The results indicate that threshold stress values for continuous flow conditions cannot be transferred to quasi static flow conditions interrupted by short fluid exchange events.